Young Learners' Perceptions on the Implementation of Online English Proficiency Test (Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
The present study made use of Cambridge Online English Test for Children and Young Learner to explore how young learners perceived the implementation of an online test and to what extent the ICT backgrounds and English exposures correlated to their online English test achievement. Three data collection strategies were used to gather the data that involved second to sixth-grade elementary school students as the participants. The instruments were: 1) Online English Proficiency Test for Young Learners; 2) observation field notes; and (3) interviews. The findings revealed that students' test scores diverse as their grade levels were also various. The mean score was 10.53 which could be categorized into Movers level which was in the middle level. It was also found that the three-quarter of the participants declared that they preferred having an online test as it gave them new experiences and comfortable feeling with taking a test on laptop or smartphones. From further investigation to the randomly selected six students, it was revealed three factors were majorly influential for young learners in benefitting the digital technology use. They were: 1) family socio-economic background; 2) parental involvement in children's digital media use; and 3) learners' personal motivation in using the digital media.